Spectral and Thermal Degradation of Melamine Cyanurate. (6th March 2013) - Sangeetha, V.; Kanagathara, N.; Sumathi, R.; Sivakumar, N.; Anbalagan, G.
Abstract : Melamine cyanurate, an organic crystalline complex was, synthesized by evaporation of an aqueous solution containing equimolar quantities of melamine and cyanuric acid. The synthesized compound has been subjected to various characterizations like Powder XRD, FT-IR, TG-DTG, SEM, and SHG. The presence of sharp diffraction peaks in the XRD confirms that the products are highly crystalline. The average particle size was calculated using the Debye-Scherrer formula, and it was found to be 3.067 μ m. Thermal behavior of the grown crystal has been studied by TG-DTG analysis. From TG-DTG, it is found that the title crystal possesses good thermal stability. The activation energy was calculated using the Broido, Coats-Redfern, and Horowitz-Metzger methods. A sharp peak exothermic peak at 405.40°C was assigned as the melting point of the title material. SEM reveals the morphology of the synthesized salt. No detectable signal was observed during the Kurtz-Perry technique.